2010
DOI: 10.1080/09540120903311508
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of consent: women's experiences testing for HIV at an antenatal clinic in Durban, South Africa

Abstract: Informed consent has historically been a cornerstone to ensuring autonomy during HIV testing. However, recent changes to global guidance on HIV testing have led to substantial debate on what policy provisions are necessary to ensure that consent remains meaningful in the context of testing. Despite disproportionate rates of testing during pregnancy, pregnant women's perspectives on the HIV testing process are underrepresented in the testing discourse. This study explores women's experiences with HIV testing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 18 publications
(16 reference statements)
2
39
0
Order By: Relevance
“…37 In our review, evidence from four studies, the majority involving small groups of pregnant women, indicated that patients were not always aware they had the right to decline HTC in antenatal clinics, perhaps because of the power balance between patients and health-care providers. 29,31 However, studies in other regions suggest that women may find the routine offer of HTC acceptable because it "normalizes" the process of HTC. 38 Our review has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…37 In our review, evidence from four studies, the majority involving small groups of pregnant women, indicated that patients were not always aware they had the right to decline HTC in antenatal clinics, perhaps because of the power balance between patients and health-care providers. 29,31 However, studies in other regions suggest that women may find the routine offer of HTC acceptable because it "normalizes" the process of HTC. 38 Our review has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies that reported on the acceptability of PITC included only small samples of women and did not involve interviews with women who declined an offer of HTC. 28,31,32 In addition, the studies included in our review are subject to their own limitations: the majority were nonrandomized studies and the difficulty of reporting and synthesizing evidence from nonrandomized studies is well documented. 39 Moreover, studies were subject to acquiescence bias 40 and, as the questions posed to patients were different in each study, it was difficult to compare their findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in Kenya (as elsewhere), considerable variation in testing uptake and return for follow up between different testing sites has been reported, indicating that specific site factors have an impact on the patient experience (Anand et al, 2009). A number of qualitative studies highlight that patients can feel pressured into testing, are mistrustful of healthcare staff or report poor quality care (Delva, Mutunga, Quaghebeur, & Temmerman, 2006;Groves, Maman, Msomi, Makhanya, & Moodley, 2010;Hamilton et al, 2008;Painter et al, 2004 (National AIDS and STD Control Programme, 2006). However, a recent evaluation of the PITC national training programme found that only 30% of health facilities were fully implementing PITC citing staff shortages, lack of space and low staff morale as associated factors (Kathambana et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%